On Maturity Measures of the Public Debt: Comment - Bowers, D. A. (Quarterly Journal of Economics, 1965)
Journal Article On Maturity Measures of the Public Debt: Comment Get access D. A. Bowers D. A. Bowers Bowery Savings Bank, New York Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 79, Issue 2, May 1965, Pages 317–321, https://doi.org/10.2307/1880636 Published: 01 May 1965